Experiences from the field chilean healthcare providers’ perspectives on partner notification for syphilis: a qualitative case study - Guaita, Nicole Ghislaine Iturrieta; Smith, Meredith Jane Temple; Tomnay, Jane Elizabeth (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Introduction: Partner Notification (NP) has long been considered an essential strategy for the control of sexually transmitted infections (STIs). Although the delivery of clinical services for STIs has improved in Chile, syphilis in the general population is one of the most commonly reported STIs. Objective: To understand PN current practices and challenges, we explored health care providers’ (HCPs) perspectives about PN for syphilis in public health services in Chile. Methods: Semi-structured interviews were conducted with HCPs in 14 primary health care centres and 6 sexual health units located at two regional Health Services as well as with key informants from different backgrounds. Interviews were transcribed verbatim and coded using QSR International’s NVivo 11 PRO Software, for cross-case thematic analysis, which followed an inductive approach. Selected quotes were translated from Spanish to English. Consensus on codes and themes was reached by the multi-disciplinary research team. Results: A total of 58 interviews were conducted. Forty-eight HCPs were interviewed across both Health Services; most with midwives with more than 10 years of work experience; and ten were key informants. Participants acknowledged PN as a syphilis control strategy with patient referral being the most common approach. Participants commented that index cases do not provide information about their partners easily and the delivery of PN is further impacted by gender and the socio-cultural context of Chile. PN was perceived by HCPs as an exhausting and difficult process. Conclusion: This is the first study to identify the perceptions of Chilean HCPs about PN for syphilis. PN is a valuable strategy for syphilis control in Chile; however, our findings suggest that HCPs consider this strategy a challenge both for them and for the Chilean population. Improving current practices and increasing awareness about PN would strengthen the work that has been done by HCPs for syphilis control and enhance the long-term impact of existing policies.